Synthesis of mesoporous TiO2 structures through P123 copolymer as the structural directing agent and assessment of their performance in dye-sensitized solar cells. (August 2016) - Abdolahi Sadatlu, Mohamad Amin; Mozaffari, Naeimeh
Graphical abstract: Highlights: Mesoporous TiO2 structures were synthesized exploiting P123 copolymer template. Mesoporous structures had narrow size distribution with high specific surface area. TiO2 powder and films were used in DSSCs in two monolayer and doublelayer forms. Doublelayer cell had higher efficiency due to the presence of mesoporous thin film. Abstract: A novel and efficacious strategy was implemented for creation of mesoporous TiO2 films and powder through an integration of sol–gel and evaporation-induced self-assembly (EISA) processes aided by triblock Pluronic P123. A mesoporous crack-free thin film with virtual thickness of 300 nm was attained under 10% relative humidity aging, for 72 h at the low temperature of 5 °C. Further, the TiO2 film with porous structure has been formed from conventional paste, exploiting as-prepared mesoporous titania powder. The X-ray Diffraction (XRD) of synthesized mesoporous powder disclosed formation of anatase phase as well as rutile phase, in such a manner that the latter constituted a very small minority. Moreover, Brunauer–Emmett–Teller (BET) and Barrett–Joyner–Helenda (BJH) proved that the isotherm pertaining to synthesized powder implies a combination of types II and IV which are related to mesoporous material with average pore size of 5.8 nm and BET surface area of 114 m 2 /g. Owing to the quantum size effect, diffuse reflection spectroscopy of prepared mesoporous TiO2 powder denoted a blue shift by comparison with that of bulk TiO2 . The mesoporous TiO2 film which has been prepared under optimized circumstances, possesses appropriate microstructural and optical properties so that it can be utilized for dye-sensitized solar cell (DSSC) applications. In order to delve profoundly into the effect of TiO2 thin film, two types of monolayer and doublelayer DSSCs were made. In light of the achieved results, the doublelayer cell indicated superior power conversion efficiency and short circuit current density of 8.05% and 18.27 mA/cm 2, respectively.